Beberapa Aspek Tamadun Melayu, India, China dan Jepun - Esa Khalid; Mohd. Azhar Abd Rahman (Penerbit Universiti Teknologi Malaysia, 2004)
Aspects of civilization of Malay, Indian, Chinese, and Japanese politic, economic, and sociocultural contributions to the development of Asia